MULTIDIMENSIONAL CHARACTERISTICS OF TEACHER’S PROFESSIONAL COMPETENCE- CHALLENGE AND PERSPECTIVES DURING EDUCATION TRANSFORMATION PROCESS - Jurs, Pāvels; Kulberga, Inta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The issue of teacher’s professional competence is multidimensional and multifaceted, it depends on several aspects, including educational policy, system implemented in every country and the particular educational establishment, which the educator works for. Being aware of the current pedagogical reality, challenges of the education system, pupils’ needs and manifold learning and teaching strategies, educators need knowledge, skills and experience of different levels formed for each particular individual in combination of education and experience with their physical, psychological and mental abilities. The goal of the article is to identify the structure of teacher’s professional competence being conscious of the theoretical and normative framework on the international and national level. In the article the theoretical research methods (method of comparison and critical thinking) and empirical research methods (data collection and document analysis) have been applied. In the society, educational institutions, also being aware of the transformation process in the education content and branch, there is a demand for teachers with a high level of professional competence. Education policy makers have set a very broad and extensive professional competence standard, which includes in itself both aspects related to the professional activity and individual characteristics, features and values. At the same time, there are various theoretical approaches which describe the framework of teacher’s professional competence and its multidimensional characteristic. The authors of the article have identified general knowledge, skills and attitude, as well as pedagogical knowledge, skills and attitude in the framework of the teacher’s professional competence structure.